Increased Reliance on Value-based Decision Processes Following Motor Cortex Disruption - Zénon, Alexandre; Klein, Pierre-Alexandre; Alamia, Andrea; Boursoit, François; Wilhelm, Emmanuelle; Duque, Julie (Brain stimulation, 2015)
During motor decision making, the neural activity in primary motor cortex (M1) encodes dynamically the competition occurring between potential action plans. A common view is that M1 represents the unfolding of the outcome of a decision process taking place upstream. Yet, M1 could also be directly involved in the decision process. Here we tested this hypothesis by assessing the effect of M1 disruption on a motor decision-making task. We applied continuous theta burst stimulation (cTBS) to inhibit either left or right M1 in different groups of subjects and included a third control group with no stimulation. Following cTBS, participants performed a task that required them to choose between two finger key-presses with the right hand according to both perceptual and value-based information. Effects were assessed by means of generalized linear mixed models and computational simulations. In all three groups, subjects relied both on perceptual (P < 0.0001) and value-based information (P = 0.003) to reach a decision. Yet, left M1 disruption led to an increased reliance on value-based information (P = 0.03). This result was confirmed by a computational model showing an increased weight of the valued-based process on the right hand finger choices following left M1 cTBS (P < 0.01). These results indicate that M1 is involved in motor decision making, possibly by weighting the final integration of multiple sources of evidence driving motor behaviors. •We used cTBS to disrupt M1 functioning during right hand finger choices•Choices relied on perceptual and value-based information•Left M1 disruption led to an increased reliance on value-based information whereas right M1 disruption tended to decrease reliance on value-based processes•These results indicate that M1 is involved in motor decision making, possibly by weighting the final integration of multiple sources of evidence.